3-Homogeneous groups and flag-transitive 6-(v, k, 3) designs. (3rd April 2018) - Liao, Xiaolian; Li, Shangzhao; Chen, Guohua
Abstract: The classification of a flag-transitive designs is an important subject on algebraic combinatorics. In this paper, we mainly discuss flag-transitive designs. Using the classification theorem of 3 – homogeneous permutation groups, the classification of flag-transitive 6 – ( v, k, 3) designs can be discussed.